WISATA MUSEUM BERBASIS EDUTAINMENT DI JAWA TIMUR PARK KOTA BATU, JAWA TIMUR - Rahmatin, Leily Suci; Mahagangga, I Gst. Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2016)
The concept of learning in a tourist attraction in Jawa Timur Park Batu City East Java increasingly delivering innovation especially in the development of the museum with the concept of edutainment, museum with a model of postmodern. This study is important because in addition to the development of tourism in tourist attraction Jawa Timur Park. Concept of development used also gives an appeal that will attract the curiosity of tourists to visit. The use of qualitative methods with data collecting technique observation, interview and documentation is done to get the data corresponding to this research, so that data on tourist attraction in East Java park with the concept of edutainment can describe the concept of postmodern museum tours. Jawa Timur Park is a tourist attraction with edutainment concept that combines seven methods museum by using audiovisual media and methods of scouting and dialogue, so that the application of the concept of education in tourism is more interesting to do.
Keywords: Museum, edutainment, Jawa Timur Park.